Preparing for old age in a geragogic approach. The conceptual assumptions for gerontological education of people aged 50+ “Towards a dignified and successful old age” - Anna Maria Leszczyńska-Rejchert (Journal of Modern Science)
Objectives The aim of this paper is to present a concept of gerontological education for people aged 50+ “Towards a dignified and successful old age” as part of the preparation for old age in a geragogic approach.